PENDIDIKAN UNTUK MEMECAHKAN MASALAH BANGSA MELALUI PENINGKATAN PROFESIONALISME GURU (Belajar dari Pengalaman Jepang) - Purwantiningsih, Ary; Suharso, Pudjo; Ismaya, Erik Aditia (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2018)
The purpose of this study is to analyze the efforts of the Japanese Government in solving educational problems after the second world war. The research method used is library research. The results of the study found that one of the advances in education in Japan was then used as an instrument to solve the nation's problems, namely through the improvement and development of professional teachers. By building professional teachers, Japan is now one of the mecca of the advancement of education from the East. Education in Japan is known as education on a philosophical basis of developers other than Taiwan, while Western world education is based on inventors.